Marijuana induced spontaneous pneumomediastinum - Chahat Puri; Kyunghoon Rhee; Vignesh K. Harish; Donald Slack (Greater Baltimore Medical Center, 2021)
Spontaneous pneumomediastinum (SPM), a rare occurrence, is defined by the presence of extraluminal gas in the mediastinum in the absence of trauma or underlying parenchymal disease. It is usually benign and has been associated with the inhalation of marijuana, cocaine, and amphetamines. The breathing maneuvers along with cyclical vomiting have been postulated as the underlying etiology. We present a case of a 27-year-old previously healthy male who presented with sudden onset chest pain and was found to have marijuana-induced pneumomediastinum.